DEVELOPMENT OF AN INTEGRATED METRÔ-BUS TRANSPORTATION SYSTEM USING THE MATHEMATICAL SOFTWARE - Heilbron, Rafael Cabidolusso Lavalle; Silva, Corbiniano; Heilbron Filho, Paulo Fernando Lavalle; Lacerda, Gleide Borges Moraes (Revista Internacional de Ciências, 2019)
The article shows the application of a program developed in mathematical platform, used to organize the urban transport that involves a system of bus lines conjugated for collective use. Three different bus lines were considered, connecting different neighborhoods. The results show the number of buses required, estimated times, arrival and departure times for three bus lines, from a hypothetical location, based on simulated data, showing the potential of the program to develop an integrated system with the subway. The program can be easily extended, allowing the inclusion of more bus lines and immediate results for any desired change / insertion of data, allowing a better and faster evaluation of the problem. The study and its results present an important tool of support and decision making to subsidize the urban transport planning of medium and large cities.